(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Trichotillomania is obsessive compulsive related disorder which causes significant distress or impairment. It can be precipitated by various stress factors in children. A 12-year-old girl presented with the complaints of pulling off hair from one half of scalp, headache, aches and pains in leg with un-refreshed sleep. History revealed she had been suffering from nocturnal enuresis which was untreated and resulted in maltreatment and caused her emotional anguish. Her trichotillomania was a done in a habitual way along with rumination later turned compulsive and irresistible. She was treated with integrated approach of pharmacotherapy and behavioral treatment which resulted complete diminution of her symptoms. J Bangladesh Coll Phys Surg 2024; 42: 289-291